Safety climate and work stress in university administration staff - Yunus, Shalsabilla; Doda, Diana Vanda Daturara; Maino, Irny Evita (Universitas Gadjah Mada, 2023)
Purpose: Workers can be exposed to work stress that can cause accidents. As a center for the development of science, universities cannot avoid the dangers and risks that can threaten safety. In this case, there is a need for an approach to workplace safety through applying a safety climate that is useful for providing a sense of security and comfort and increasing safety behavior. Method: This survey used 164 respondents who work at a university, asking questions about gender, age, work experience, stress level, and perception of safety. The analysis included univariate analysis using frequency and percentage; bivariate and multivariate analysis using a binary logistic regression test. Result: Most respondents were women, middle-aged, and had worked for more than 21 years. More than half of the respondents experienced stress and rated the safety climate as low. Male respondents had a higher chance of experiencing stress than female respondents. Respondents with a lower level of safety climate were more likely to report work stress than those respondents with a high level of safety climate. Conclusion: Respondents’ perception of the safety climate affected their stress levels, and managers should consider this when designing programs to prevent stress at work.